Inhibitory effect of an ethanol extract of sembung leaves (Blumea balsamifera) on the growth of Helicobacter pylori: In vitro approach - Ariastuti, Indria; Suardana, Anak Agung Komang; Wahyudi, I Wayan (PT. Mega Science Indonesia, 2025)
Helicobacter pylori infection is a global health problem with a high prevalence in developing countries and plays a role in the pathogenesis of various gastrointestinal disorders. Antibiotic resistance is a major challenge in the eradication of H. pylori, prompting the exploration of alternative antibacterial agents derived from traditional medicinal plants. To analyze the antibacterial activity of an ethanol extract of sembung leaves (Blumea balsamifera) against Helicobacter pylori growth in vitro. This experimental study used a posttest control group design with five concentrations of the ethanol extract of sembung leaves (10%, 20%, 40%, 60%, and 80%). The extraction was performed via the maceration method with 96% ethanol. Antibacterial activity was tested via the Kirby–Bauer disk diffusion method on Mueller–Hinton agar medium. The inhibition zone diameter data were analyzed via the Kruskal‒Wallis and Mann‒Whitney tests with a 95% confidence level. None of the concentrations of the Sembung leaf ethanol extract produced an inhibition zone against H. pylori, with a diameter of 0 ± 0 mm in all the treatment groups. The positive control exhibited an inhibition zone of 23.15 ± 0.28 mm. The Kruskal‒Wallis test revealed a significant difference (p = 0.000). However, the Mann‒Whitney U test confirmed that there was no significant difference between the negative control and all extract concentrations (p=1.000). Ethanol extracts of Blumea balsamifera leaves at concentrations ranging from 10–80% did not exhibit antibacterial activity against H. pylori in vitro, as determined via the disk diffusion method.